A view from above: using Unmanned Aerial Vehicles (UAVs) to enhance ecological understanding of lianas in tropical forest canopies - Waite, Catherine E. (2020)
Lianas play integral roles in structuring community composition, forest regeneration, the maintenance of species diversity and whole-forest level ecosystem processes in tropical forests. With increasing disturbances to forests worldwide, the relative importance of lianas as players in many areas of forest dynamics is expected to increase, with important ramifications for the global carbon cycle. However, our knowledge of lianas is incomplete and biased: (i) towards the Neotropics; and (ii) against the canopy, yet the canopy is where lianas proliferate most. Research in these areas is hampered by the logistical difficulties of studying lianas; the fact that they are time-consuming to survey, and that it is difficult to quantify what is going on in the canopy. This thesis enhances ecological understanding of lianas in tropical forest tree crowns, focusing on the lesser studied Palaeotropics. The development of a novel method to enable faster, cheaper and more canopy-centred assessment of liana than possible with traditional assessment methods is vital for this. A lightweight unmanned aerial vehicle (UAV) was used to assess liana infestation of tropical forest tree canopies in Sabah, Malaysia. By visually interpreting the images, the UAV-derived liana infestation estimates were compared with those derived from traditional ground methods of liana infestation assessment to determine the validity, strengths and weaknesses of using UAVs as a new method for assessing liana infestation of tree canopies. These data were then used to map and monitor liana load in tree crowns: (i) spatially, to elucidate liana-environmental relationships; and (ii) temporally, to monitor the canopy response, including changes in liana infestation, to El Niño drought. UAV-derived estimates of liana infestation correlated strongly with ground-derived data at individual tree and plot level, and across multiple forest types and spatial resolutions. Furthermore, the UAV surveys improved liana infestation assessment for upper canopy layers and were considerably faster and more cost-efficient than ground-based surveys. Liana infestation was significantly spatially aggregated, with tree canopy height and presence of canopy gaps being the most important variables influencing this. Taller trees were less often and less heavily infested by lianas while liana infestation occurred more often and to greater extents in close proximity to canopy gaps. Temporally, tree-level liana infestation and crown area showed significant increases in the aftermath of the 2015/16 El Niño whereas crown greenness and tree leaf cover showed a significant decrease. Furthermore, liana cover was significantly higher for trees that experienced mortality in the aftermath of the El Niño than for those that did not. This thesis presents a novel UAV-based method of capturing data that can be used to assess liana infestation of tropical forest tree crowns at least as accurately as traditional ground data. This novel method promotes reproducibility of results and quality control, and enables additional variables to be derived from the image data. It is more cost-effective, time-efficient and covers larger geographical extents than traditional ground surveys, enabling more comprehensive monitoring of changes in liana infestation over space and time. By utilising the new UAV method, this thesis presents: (i) the largest and most comprehensive continuous assessment of Palaeotropical tree crown liana infestation, and analysis of environmental variables that may influence this, to date; and (ii) the first study assessing short-term temporal change in liana canopy cover and associated alterations in the forest canopy using UAV image data. Examining how and why lianas are distributed in the forest canopy and how this changes through time may help us to determine what variables could determine increases in lianas with environmental change in the future, with important implications for tropical forest carbon storage and sequestration, and provide a step towards more comprehensive testing of ecological theory in tropical forests.